2014
DOI: 10.1074/jbc.m114.558924
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside-catabolizing Enzymes in Mycoplasma-infected Tumor Cell Cultures Compromise the Cytostatic Activity of the Anticancer Drug Gemcitabine

Abstract: Background: Gemcitabine is used to treat solid tumors. Some mycoplasmas preferentially colonize tumors in patients. Results: Mycoplasma-encoded cytidine deaminase and pyrimidine nucleoside phosphorylase compromise the cytostatic/antitumor activity of gemcitabine in mycoplasma-infected tumor cell cultures and xenografts in mice. Conclusion: Tumor-associated mycoplasmas may decrease the therapeutic efficiency of gemcitabine. Significance: Current treatment of mycoplasma-infected tumors with gemcitabine may be su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
90
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 46 publications
4
90
0
Order By: Relevance
“…This experiment revealed that conditioned medium from M. hyorhinis -infected HDFs metabolizes gemcitabine into its deaminated inactive metabolite 2′,2′-difluorodeoxyuridine (7) as has been previously reported (8, 9) (Fig. 1C and fig.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…This experiment revealed that conditioned medium from M. hyorhinis -infected HDFs metabolizes gemcitabine into its deaminated inactive metabolite 2′,2′-difluorodeoxyuridine (7) as has been previously reported (8, 9) (Fig. 1C and fig.…”
supporting
confidence: 82%
“…To find the bacterial genes involved in gemcitabine resistance, we first considered the bacterial enzyme cytidine deaminase (CDD) because it was previously shown to mediate gemcitabine deamination by Mycoplasma (8). According to the Kyoto Encyclopedia of Genes and Genomes (KEGG) (10), of 2,674 bacterial species analyzed, 11.4% contained an ∼880-nucleotide long form of CDD (CDD L ), 44.4% contained a ∼400-nucleotide short form (CDD S ), and 44.2% lacked CDD entirely (Fig.…”
mentioning
confidence: 99%
“…The cytidine deaminase enzyme of M. hyorhinis might be responsible for converting gemcitabine into an inactive form through a metabolic process called deamination 8 .…”
Section: H R I St I a N J O B I Nmentioning
confidence: 99%
“…Such optimization has conventionally been achieved either by testing combinations of variables manually or by using machinelearning techniques. Each of these approaches has advantages in different situations and both were instrumental in the discovery of the Higgs boson 7,8 in 2012.…”
Section: St E V E N S C H R a M Mmentioning
confidence: 99%
“…Such optimization has conventionally been achieved either by testing combinations of variables manually or by using machinelearning techniques. Each of these approaches has advantages in different situations and both were instrumental in the discovery of the Higgs boson 7,8 in 2012. Human-constructed classifiers often have a physically intuitive meaning and can be optimized using a relatively small amount of data.…”
Section: St E V E N S C H R a M Mmentioning
confidence: 99%